Stemness Signature of Equine Marrow-derived Mesenchymal Stem Cells - Zahedi, Morteza (Int J Stem Cells, 2017)
BACKGROUND: Application of competent cells such as mesenchymal stem cells (MSCs) for treatment of musculoskeletal disorders in equine athletes is increasingly needed. Moreover, similarities of horse and human in size, load and types of joint injuries, make horse as a good model for MSCs therapy studies. This study was designed to isolate and characterize stemness signature of equine bone marrow-derived mesenchymal stem cells (BM-MSCs). METHODS: BM of three mares was aspirated and the mononuclear cells (MNCs) were isolated using density gradient. The primary MNCs were cultured and analyzed after tree passages (P3) for growth characteristics, differentiation potentials, and the expression of genes including CD29, CD34, CD44, CD90, CD105, MHC-I, MHC-II and pluripotency related genes (Nanog, Oct-4, Sox-2, SSEA-1, -3, -4) using RT-PCR or immunocytochemistry techniques. RESULTS: The isolated cells in P3 were adherent and fibroblast-like in shape with doubling times of 78.15 h. Their clonogenic capacity was 8.67±4% and they were able to differentiate to osteogenic, adipogenic and chondrogenic lineages. Cells showed expression of CD29, CD44, CD90, MHC-I and Sox-2 while no expression for CD34, MHC-II, CD105, and pluripotency stemness markers was detected. CONCLUSIONS: In conclusion, data showed that isolated cells have the basic and minimal criteria for MSCs, however, expressing only one pluripotency gene (sox-2).